2021
DOI: 10.3389/frai.2021.673527
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Prediction and Mortality Risk Calculation for COVID-19 Using Machine Learning

Abstract: Background: Early prediction of symptoms and mortality risks for COVID-19 patients would improve healthcare outcomes, allow for the appropriate distribution of healthcare resources, reduce healthcare costs, aid in vaccine prioritization and self-isolation strategies, and thus reduce the prevalence of the disease. Such publicly accessible prediction models are lacking, however.Methods: Based on a comprehensive evaluation of existing machine learning (ML) methods, we created two models based solely on the age, g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…A number of studies have investigated the risk factors affecting COVID-19 infections (34,35). Elevated inflammatory cytokines such as interleukin-6 (IL-6), granulocyte colonystimulating factor (G-CSF), interferon gamma-induced protein 10 (IP-10), and interferon (IFN)-γ have been proposed as poor prognostic factors for COVID-19 patients (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the risk factors affecting COVID-19 infections (34,35). Elevated inflammatory cytokines such as interleukin-6 (IL-6), granulocyte colonystimulating factor (G-CSF), interferon gamma-induced protein 10 (IP-10), and interferon (IFN)-γ have been proposed as poor prognostic factors for COVID-19 patients (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In general the prevalence of COVID-19 symptoms differ depending on the studied population. For example, in an Iranian study of 23,749 patients from 74 hospitals in Teheran, the most prevalent symptoms were cough (50.51%), respiratory distress (43.55%), muscular pain or fatigue (38.94%), gastrointestinal problems (10.4%) and headache (4.72%) ( 35 ). A Chinese meta-analysis of 38 studies with 3,062 patients found these to be fever (80.4%), cough (63.1%) and fatigue (46.0%) but not anosmia or ageusia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Till now, several general characteristics and diseased elements such as sex, age, high blood pressure, diabetes, chronic lung infection, dermatologic infection, endocrine and hepatobiliary complications, and cardiovascular manifestation are considered among the main risk factor observed during clinical managements of COVID-19 (Jordan et al, 2020;Yang et al, 2020;Jamshidi et al, 2021).…”
Section: Viral Manifestationsmentioning
confidence: 99%